Analisis SWOT Lembaga Pendidikan: - Arman Paramansyah; Zaki Wicaksono (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2023)
The background of this research is that every educational institution must be able to make the right strategy and be able to make a plan to compete in the present and in the future. The National Institute of Islamic Religion Laa Roiba Bogor is an educational institution engaged in education. the implementation of the strategy chosen by the leadership, which is an alternative strategy, can create four main strategies, namely the SO strategy (Strength and Opportunities), WO strategy (Weakness and Opportunities), ST strategy (Strength and Threats) and WT strategy (Weakness and Threats). ). This study uses a descriptive qualitative approach, this type of research is a case study. Data was collected by means of interviews, observation, documentation and questionnaires. The analytical technique used is interactive technical analysis following the concept of Miles and Huberman. The results of the SWOT analysis research can be used as maps or maps because after each form of factor is determined, the policies that will be taken as a form of priority scale in future improvements have been determined, so that what IAI-N Laa Roiba does and can carry out with full commitment, responsibility and discipline so that the realization of quality, integrated educational institutions, and can produce students who become human resources who excel in academics, have good morals and are able to be competitive in society in realizing the Tridarma of higher education. Keywords: SWOT Analysis, Alternative Strategy, IAI-N Laa Roiba